Mild evolution of the stellar metallicity gradients of disc galaxies - Tissera, Patricia Beatriz (2017)
Context. The metallicity gradients of the stellar populations in disc galaxies and their evolution store relevant information on the disc formation history and on those processes which could mix stars a posteriori, such as migration, bars and/or galaxy-galaxy interactions. Aims. We aim to investigate the evolution of the metallicity gradients of the whole stellar populations in disc components of simulated galaxies in a cosmological context. Methods. We analyse simulated disc galaxies selected from a cosmological hydrodynamical simulation that includes chemical evolution and a physically motivated supernova feedback capable of driving mass-loaded galactic winds. Results. We detect a mild evolution with redshift in the metallicity slopes of − 0.02 ± 0.01 dex kpc-1 from z ~ 1. If the metallicity profiles are normalised by the effective radius of the stellar disc, the slopes show no clear evolution for z< 1, with a median value of approximately − 0.23 dex reff-1. As a function of stellar mass, we find that metallicity gradients steepen for stellar masses smaller than ~1010.3M⊙ while the trend reverses for higher stellar masses, in the redshift range z = [ 0,1 ]. Galaxies with small stellar masses have discs with larger reff and flatter metallicity gradients than expected. We detect migration albeit weaker than in previous works. Conclusions. Our stellar discs show a mild evolution of the stellar metallicity slopes up to z ~ 1, which is well-matched by the evolution calculated archeologically from the abundance distributions of mono-age stellar populations at z ~ 0. The dispersion in the relations allows for stronger individual evolutions. Overall, supernova feedback could explain the trends but an impact of migration can not be totally discarded. Galaxy-galaxy interactions or small satellite accretions can also contribute to modify the metallicity profiles in the outer parts. Disentangling the effects of these processes for individual galaxies is still a challenge in a cosmological context.